A Risk Management Approach to Global Pandemics of Infectious Disease and Anti-Microbial Resistance - Annie Sparrow; Meghan Smith-Torino; Samuel M. Shamamba; Bisimwa Chirakarhula; Maranatha A. Lwaboshi; Christine Stabell Benn; Konstantin Chumakov (Tropical Medicine and Infectious Disease)
Pandemics of infectious disease and growing anti-microbial resistance (AMR) pose major threats to global health, trade, and security. Conflict and climate change compound and accelerate these threats. The One Health approach recognizes the interconnectedness of human, animal, and environmental health, but is grounded in the biomedical model, which reduces health to the absence of disease. Biomedical responses are insufficient to meet the challenges. The COVID-19 pandemic is the most recent example of the failure of this biomedical model to address global threats, the limitations of laboratory-based surveillance, and the exclusive focus on vaccination for disease control. This paper examines the current paradigm through the lens of polio and the global campaign to eradicate it, as well as other infectious threats including mpox and drug-resistant tuberculosis, particularly in the context of armed conflict. Decades before vaccines became widely available, public health measures—ventilation, chlorination, nutrition and sanitation— led to longer, healthier, and even taller lives. Chlorine, our primary tool of public health, conquered cholera and transformed infection control in hospitals. The World Health Organization (WHO), part of the One Health alliance, focuses mainly on antibiotics and vaccines to reduce deaths due to superbugs and largely ignores the critical role of chlorine to control water-borne diseases (including polio) and other infections. Moreover, the One Health approach ignores armed conflict. Contemporary wars are characterized by indiscriminate bombing of civilians, attacks targeting healthcare, mass displacement and lack of humanitarian access, conditions which drive polio outbreaks and incubate superbugs. We discuss the growing trend of attacks on healthcare and differentiate between types: community-driven attacks targeting vaccinators in regions like Pakistan, and state-sponsored attacks by governments such as those of Syria and Russia that weaponize healthcare to deliberately harm whole populations. Both fuel outbreaks of disease. These distinct motivations necessitate tailored responses, yet the WHO aggregates these attacks in a manner that hampers effective intervention. While antimicrobial resistance is predictable, the escalating pandemic is the consequence of our reliance on antibiotics and commitment to a biomedical model that now borders on pathological. Our analysis reveals the international indenture to the biomedical model as the basis of disease control is the root driver of AMR and vaccine-derived polio. The unique power of vaccines is reduced by vaccination-only strategy, and in fact breeds vaccine-derived polio. The non-specific effects of vaccines must be leveraged, and universal vaccination must be supplemented by international investment in water chlorination. This will reduce health costs and strengthen global health security. While vaccines are an important weapon to combat pandemics and AMR, they must be accompanied by the entire arsenal of public health interventions.